Russian multicentre type 2 diabetes screening program in patients with cardiovascular disease - Marina Vladimirovna Shestakova; Irina Evgenievna Chazova; Ekaterina Alekseevna Shestakova (Сахарный диабет)
Aim.To evaluate the prevalence of undiagnosed type 2 diabetes mellitus (T2DM) among patients with cardiovascular disease.Materials and methods.T2DM screening programs among patients with cardiovascular disease were held from 2013 to 2014 in several Russian cities. In total, 1001 patients aged ≥40 years with hypertension and/or atherosclerotic disease and without prior diagnosis of T2DM were screened in outpatient cardiology clinics. T2DM diagnosis was based on fasting plasma glucose levels, glycated haemoglobin (HbA1c) and/or oral glucose tolerance test (OGTT) results. Blood pressure (BP), family history of T2DM, cardiovascular disease, total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL) and triglyceride levels were analysed.Results.Fasting glucose was measured in 1000 (99.8%) patients, HbA1c was measured in in 623 (62.2%) and OGTT was performed in 286 (2.6%). Fasting glucose detected 8% of newly diagnosed T2DM; among patients who underwentHbA1c measurement, the prevalence of T2DM was 10.91%, and among patients who underwent OGTT, the prevalence was 13.99%. Depending on the chosen test, the prevalence of undiagnosed pre-diabetes (impaired fasting glycaemia and impaired glucose tolerance) was in the range of 14.4%–36.4%. The majority of patients with T2DM diagnosed by OGTT did not have target blood pressure and lipid levels; 67.5% had elevated systolic BP, 47.5% had elevated diastolic BP, 90.9% had high LDL (≥1.8 mmol/l) and 52.9% had high triglyceride levels (≥1.7 mmol/l).Conclusion.A high prevalence of undiagnosed T2DM (from 8% to 13.99%, depending on the diagnostic criteria) and pre-diabetic state in patients with cardiovascular disease may require screening for T2DM in this high-risk group.